The quality of higher education during the Covid-19 pandemic and the prospects for post-secondary education (Journal of Educational Sciences, 2021)
The COVID-19 pandemic, which spread widely around the world at the beginning of 2020 and continues to this day, has seriously affected the field of higher education. In a short time, it forced to change the traditional form of education to distance learning. Most of the world’s universities were not ready for this: neither technically nor conceptually. As a result, there is widespread criticism of online education, the quality of training is declining, the negative consequences of covid education are being actualized. At the same time, researchers are looking for new vectors of development, studying the mistakes of the past, realizing that the pandemic did not have a special impact, but only aggravated the problems already existing in the education system. In this regard, a study was conducted in Kazakhstan, the purpose of which was to study the quality of higher education during the pandemic through the eyes of students, their preferences and proposals for reforming higher education. As part of this study, a sociological survey was conducted that covered a thousand students from different regions of the Republic of Kazakhstan. This study will complement the ideas about the prospects of higher education after the pandemic, and the results will be useful for teachers of higher educational institutions, philosophers of education and anyone interested in the problems of higher education. Key words: philosophy of education, pandemic, higher education, quality of education, distance education, post-secondary education.